Motor Skill Training May Restore Impaired Corticospinal Tract Fibers in Children With Cerebral Palsy. (June 2020) - Bleyenheuft, Yannick; Dricot, Laurence; Ebner-Karestinos, Daniela; Paradis, Julie; Saussez, Geoffroy; Renders, Anne; De Volder, Anne; Araneda, Rodrigo; Gordon, Andrew M.; Friel, Kathleen M.
Background . In children with unilateral cerebral palsy (UCP), the fibers of the corticospinal tract (CST) emerging from the lesioned hemisphere are damaged following the initial brain injury. The extent to which the integrity of these fibers is restorable with training is unknown. Objective . To assess changes in CST integrity in children with UCP following Hand-and-Arm-Bimanual-Intensive-Therapy-Including-Lower-Extremity (HABIT-ILE) compared to a control group. Methods . Forty-four children with UCP participated in this study. Integrity of the CSTs was measured using diffusion tensor imaging before and after 2 weeks of HABIT-ILE (treatment group, n = 23) or 2 weeks apart without intensive treatment (control group, n = 18). Fractional anisotropy (FA) and mean diffusivity (MD) were the endpoints for assessing the integrity of CST. Results . As highlighted in our whole tract analysis, the FA of the CST originating from the nonlesioned and lesioned hemispheres increased significantly after therapy in the treatment group compared to the control group (group * test session interaction: P < .001 and P = .049, respectively). A decrease in MD was also observed in the CST emerging from the nonlesioned and lesioned hemispheres (group * time interaction: both P < .001). In addition, changes in manual ability correlated with changes in FA in both CSTs ( r = 0.463, P = .024; r = 0.643, P < .001) and changes in MD in CST emerging from nonlesioned hemisphere ( r = −0.662, P < .001). Conclusions . HABIT-ILE improves FA/MD in the CST and hand function of children with UCP, suggesting that CST fibers retain a capacity for functional restoration. This finding supports the application of intensive motor skill training in clinical practice for the benefit of numerous patients.